Analisis Strategi Pengembangan Bisnis dengan Pendekatan Bisnis Model Canvas (BMC) dan SWOT - Detty Agustin Riscal; Sri Sahbany (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Cinnamonstory.id is a handover and dowry decoration business that was formed in 2017. The purpose of this study is to analyze the mapping of the 9-element Business Model Canvas (BMC) business model with SWOT analysis (trends, weaknesses, opportunities, and threats), and formulate a business model development strategy Cinnamonstory.id using the SWOT matrix. The type of research used is qualitative descriptive. The analysis method in this study uses a combination of BMC analysis approach and SWOT matrix in formulating Cinnamonstrody.id business development strategy. The results of the SWOT analysis show that Cinnamonstory.id in Quadrant II is a diversification strategy. The results of the study show that training, design innovation, affordable services, responsiveness, and effective digital marketing are the keys to Cinnamonstory.id success. Develop Cinnamonstory.id by joining a network of vendors, offering consulting and leasing, recruiting, and training employees, and establishing partnerships with suppliers. Seek out new ideas, develop distinctiveness, improve operational efficiency, manage suppliers, and provide superior customer service in Cinnamonstory.id. Analyze customer feedback and sales data, allocate funds for promotions and investments, and develop marketing strategies and partnerships through social media.